Plasma citrate concentration: a possible biomarker for glaucoma in children. Issue 1 (3rd July 2017) - Michalczuk, Marta; Tadeusz, Porowski; Urban, Beata; Anna, Wasilewska; Bakunowicz- Łazarczyk, Alina
Abstract : Objectives: The main aim of the present study was to examine a possible role of plasma and urine citrate levels as glaucoma indicators in school-aged children with glaucoma diagnosis. Patients: 34 school-aged children with a glaucoma diagnosis (mean age 15.69±1.86 years) were qualified for the study group and 34 patients with no ophthalmological ailments were qualified for the control group (mean age 16.1±1.98 years). Plasma and urine citrate levels in the study and the control group (Kruskal-Wallis test) were compared. Results: Plasma citrate levels in the study (16.33±4.51 mg/L) and the control group (19.11±3.66 mg/L) were different; the statistical significance (p=0.0036). Plasma citrate concentrations were significantly lower in the study group in comparison with the control group. There were no statistically important differences between the study group (291.12±259.13 mg/24 hours; 275.82±217.57 mg/g) and the control group (434.88±357.66 mg/24 hours; 329.81±383.27 mg/g) including urine citrate level (p=0.052) and urine citrate to creatine ratio (p=0.4667). Conclusion: Plasma citrate concentration might be considered as glaucoma biomarker in paediatric population.